Outcomes of renal transplantation in patients with lupus nephritis: a single centre study in Cape Town - Almradi, Ahmed Khalifa Mohamed (Department of Medicine, 2018)
Background: Kidney disease (lupus nephritis [LN]) constitutes a feature of systemic lupus erythematosus (SLE) in up to 50 - 70% of patients with the disease. Although most LN patients are suitable for renal transplantation when they develop end stage renal disease (ESRD), the risk of recurrence of LN post-transplantation can be as high as 30%. Since the outcomes of renal transplantation in ESRD-LN patients has not been adequately studied in South Africa, the present study aims to retrospectively explore the aforementioned objective in a single centre. Methodology: The study was designed as a retrospective descriptive study of patients with LN transplanted in the renal unit of Groote Schuur Hospital, Cape Town from 1st January 2004 to 31st December 2013. Results: There were 454 patients who were transplanted in the study period of which 15/454 (3.3%) had LN. The M:F ratio of LN patients was 1:14, mean age was 25±10 years, all were known with class- IV LN and 10/15 (66.7%) received graft from a cadaveric donor. Immunosuppression was initiated in 7/15 (46.7%) with combination of cyclosporine and azathioprine; in 2/15 (13.3%) with tacrolimus and azathioprine and in 6/15 (40.0%) with Tacrolimus and MMF. All patients received corticosteroids. Recurrence of LN was seen in one patient (6.7%) who developed class V LN. Graft rejection was diagnosed in 10/15 cases (66.7%) with types of rejection noted to be acute cellular rejection in 6/15 (40%), antibody mediated rejection 1/15 (6.7%) and chronic rejection in 3/15 (20%). ESRD occurred in 3 patients (20%) with causes from antibody mediated rejection (6.7%), chronic allograft nephropathy (6.7%) and renal artery thrombosis (6.7%). Mean time to ESRD was 16.0 months. Five deaths (33.3%) occurred from sepsis in 3/15 (20%), pulmonary embolism; 1/15 (6.7%) and progressive ESRD after non-acceptance to the chronic dialysis program; 1/15 (6.7%). Mean time to death was 44.1 months. Conclusion: This study shows that recurrence of LN in the graft kidney is uncommon in South Africa. However, effort to reduce high rates of rejection and improve graft and patient survival still needs to be studied.